Neisseria gonorrhoeae–Induced Inflammatory Pyroptosis in Human Macrophages is Dependent on Intracellular Gonococci and Lipooligosaccharide. (2nd January 2018) - Ritter, Jessica Leigh; Genco, Caroline Attardo
Neisseria gonorrhoeae, the human obligate pathogen responsible for the sexually transmitted disease gonorrhea, has evolved several mechanisms to evade the host immune response. One such mechanism is the modulation of host cell death pathways. In this study, we defined cell death pathways induced by N gonorrhoeae in human monocyte-derived macrophages (MDMs). In a dose-dependent manner, N gonorrhoeae stimulation of MDMs resulted in caspase 1 and 4–dependent cell deaths, indicative of canonical and noncanonical pyroptosis, respectively. Internalization of bacteria or stimulation with lipooligosaccharide (LOS) specifically induced pyroptosis in MDMs and increased secretion of IL-1β. Collectively, our results demonstrate that N gonorrhoeae induces inflammatory pyroptosis in human macrophages due in part to intracellular LOS. We propose that this in turn may exacerbate inflammatory outcomes observed during mucosal infection.